Analytical modeling and simulation analysis of T-shaped III-V heterojunction vertical T-FET - Singh, Shailendra; Raj, Balwinder (Superlattices and microstructures, 2020)
In this paper, we have developed a new 2D compact analytical model for surface potential and drain current for III-V group heterojunction of T-shaped Vertical Tunneling FET with inherited properties of dual modulation effect. The device's surface potential is determined from the compact model, which is the most significant consideration for defining device current characteristics. There have been numerous efforts to predict the electrical characteristics of In0.53Ga0.47As as a heterojunction and to discuss the method of device improvement as a function of mole-fraction, gate-drain biasing potential, gate metal work-function. To determine the tunneling width, the dual modulation effect is used to regulate the biasing voltage at both the source and drain junction. A 2-D Poisson equation is solved for the proposed model by using parabolic approximation method with constant electric field which are used to determine the effect of In0.53Ga0.47As as a comparison to Silicon and SiGe material device. Moreover, a new expression of channel surface potential is derived that can forecast the effect of drain and gate biasing. The derived model results validation is carried out by the comparison with the results obtained by TCAD simulation. •A new 2-D compact analytical modeling analysis of surface potential model for III-V heterojunction Vertical T-shaped Tunnel FET.•By solving Poisson's equation, potential of gate-bias and drain bias have been calculated with imposed InGaAs layer and then, current has been estimated.•The Kane's Model is used for calculating the band-2-band tunneling generation rate to derive the drain current.•Most importantly, a new channel surface potential expression is derived that can forecast the effect of drain and gate biasing.•The derived model results are compared and found to be in perfect agreement with the simulated one in order to evaluate the validity of electrical parameter model.